A study on using pre-bent steel strips as seismic energy-dissipative devices. - Wang, Yen-Po (Earthquake engineering & structural dynamics.)
Buckling is usually conceived as an unstable structural behavior leading to lateral instability of axially loaded members, if not properly supported. However, a pre-bent strip would become an excellent seismic energy-dissipative device if it is deformed in a guided direction and range. Geometrically large lateral deformation of the steel strips in buckling leads to inelastic behavior of the material and dissipates energy as a consequence. The purpose of this study is to propose a new type of seismic damper in the form of braces based on pre-bent steel strips. The nonlinear elastic stiffness of monotonously loaded pre-bent strips in both compression and tension is derived. The energy-dissipative characteristics of the proposed damping device are investigated via component tests under cyclic loads. Experimental results indicate that the force?displacement relationship of pre-bent strips in cyclic loads exhibits mechanical characteristics of displacement-dependent dampers. A series of seismic performance tests has been conducted further to verify the feasibility and effectiveness of using the proposed device as seismic dampers. Encouraging test results have been obtained, suggesting feasibility of the proposed device for earthquake-resistant design.